Analysis of Participation and Willingness to Pay Community in Rural Infrastructure Development (Case Study in Pidodo Wetan Village, Kendal) - Shintia Prissillia Nainggolan; Edy Yusuf Agung Gunanto; Nenik Woyanti; Banatul Hayati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2019)
This study aims to analyze the level of participation and willingness to pay the community in rural infrastructure development. This study uses descriptive quantitative analysis in analyzing the participation rate and the Contingent Valuation Method in analyzing the willingness to pay the community. The Data used are primary and secondary data. Primary Data sourced from questionnaire result 92 respondents. Secondary Data is sourced from Pidodo Wetan Village Office. The results Showed that the level of community participation in the construction of infrastructure Pidodo Wetan village is in the high category. Form of participation is most Widely given the power and material / food. Furthermore, the average value of willingness to pay the community of Rp.10,500 with the total value of willingness to pay of Rp.13,728,000. Family income affects the value of the willingness to pay of the community, whereas gender, age, and education have no effect on the bid willingness to pay of the community.